Income inequality and household debt: Examining the impact of relative income on formal and informal debt in South Africa - Shakeba Foster (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
How does income inequality impact the propensity for and levels of formal and informal household debt? This paper assesses this question using the two most recent waves of the South African Living Conditions Survey. A range of linear models as well as a zero-inflated Poisson model are employed, and inequality is measured by a household relative deprivation index, comparing households within provinces. The results provide evidence that households with higher relative deprivation (or lower relative incomes) hold higher levels of outstanding debt, and significant proportions of debt are from informal sources. Additionally, the paper provides suggestive evidence that informal borrowing among households with lower relative incomes is not directed towards investment in capital goods but instead reflects both a tunnel effect-through investments in small-scale ventures and household financial security and a keeping-up effect- through hire purchase of furniture and appliances as social capital.
Keywords: D12; D14; D31; E26; 330; income inequality; household debt; informal debt; relative income; keeping up with the Joneses